Psychometric adaptation of the Frydenberg and Lewis test “Adolescent Coping Scales” to a group of school students in metropolitan Lima - Canessa, Beatriz (2002)
The aim of the current study was to perform a psychometric adaptation of the Frydenberg and Lewis’s test “Adolescent Coping Scales” (ACS). Participants were 1.236 students, male and female, from different socio-economic level, high, middle and low. Their ages ranged from 14 to 17 years old. Results of all the scores for the ACS Lima were shown to be reliable. It was also concluded that this test has construct validity, due to the item-test correlation for every scales demonstrataed to be significant, and factor analysis showed that the 18 scales that form the ACS are to conform the adapted version of this test for our environment, including specific items in some cases.